AMINO-ACID COMPOSITION AND GEOCHRONOMETRY BASED ON FOSSIL MOLLUSKS OF THE CASPIAN - Shlyukov A.I.; Tsyryapkin V.A.; Nedospasova L.V.; Parunin O.B. (My University, 1989)
This article presents the results of the first attempt in the USSR to use the process of racemization of amino acids for the geochronometry of Quaternary deposits. This research tool has been used elsewhere for more than 20 years, but only in the last few years, with the advent of high-efficiency chromatography, did the first quantitative estimates, revealing the potential of the amino-acid geochronometer, become available. The method is based on the process of spontaneous epimerization - the reciprocal transformation of enantiomers, a process which in nature takes place at quite low rates, so that the quantitatively measurable changes in their ratios are a function of geologic time.
Keywords: Quaternary; Cenozoic::Quaternary; Кайнозой::Четвертичная